An Analysis of 21st-Century Skills Representation in The Indonesian EFL Textbooks for Seventh Graders - Ida Ayu Putri Pradnya Utami; Untung Waluyo; Ahmad Zamzam; Henny Soepriyanti; Dewi Satria Elmiana (Jurnal Ilmiah Profesi Pendidikan, 2026)
The integration of 21st-century skills into English as a Foreign Language (EFL) textbooks is increasingly important to help students meet the challenges of global communication, technological developments, and the demands of modern education. The purpose of this study was to identify the 21st-century skills represented in the seventh-grade EFL textbooks English for Nusantara and English in Mind, how they are represented, and the differences in their representation. This study uses a qualitative descriptive research design with content analysis based on the Partnership for 21st-Century Learning (P21) framework. Data were collected through documentation techniques by identifying textbook content, such as tasks, activities, texts, visual representations, and instructions, that reflected the 12 21st-century skills. Data analysis was conducted through coding, frequency, and percentage calculations, comparative analysis, and descriptive interpretation. The findings indicate that both textbooks cover all twelve skills, but with different emphases. Critical thinking and problem-solving, communication, media literacy, and information literacy were dominant in both textbooks. In contrast, life and career skills such as flexibility and adaptability, leadership and responsibility, productivity and accountability, and initiative and self-direction were minimally represented. This study concludes that English for Nusantara emphasizes structured and directed learning, while English in Mind encourages a more communicative, collaborative, and interactive learning experience.